القيم الأخلاقية في شعر الزهد عند داود تجاني أَدَيْكِيْلَيْكُن (Ethical Values in the Poetry of Asceticism by Daud Tijani Adaikilaikun) - (Abdel Qahar Abdel Wahab al-Sarimiy), عبد القهار عبد الوهاب (مجلة الدراسات اللغوية والأدبية (Journal of Linguistic and Literary Studies), 2014)
ملخص البحث: الزهد ظاهرة نفسية عُرف له أثرٌ كبير في الشعر العربي منذ عصر الجاهلية، حين أخذ به قومٌ من نُسّاك النصارى ومن المتحنّفين، فانتشرتْ أفكار الزهد تحت تأثير الرهبنة النصرانية والتنسّك الحنفي، وشاع قسمٌ منه على ألسنة الشعراء، فظهر أوّل ما ظهر في تضاعيف القصيدة الحِكَمِية وغيرها، وما لبث أن استقلّ بنفسه، فكان ثمّة قصائدُ ومقطوعاتٌ مستقلّة، وأضحى له روّاده وعشّاقه وممثّلوه الحقيقيّون عبر العصور الأدبية العربية، إلاّ أنّه ازدهر ازدهارا ملحوظاً في العصر العبّاسي لعوامل منها السياسية والاجتماعية والأخلاقية والثقافية، ثمّ أخذ الزهد مكانه عاليا في أغراض الشعر الغنائي العربي في كل زمان ومكان راج فيه الأدب العربي حتّى عصرنا الحديث. كلّ ذلك له أثره في الأدب العربي النيجيري وعلى الشعر بالذات، فهذا البحث يهدف إلى دراسة القيم الأخلاقية في "القصيدة الدّالية الزهدية" للشاعر النيجيري الراحل الدكتور داود تيجاني أَدَيْكِيْلَيْكُنْ. وتحتوي القصيدة على ما يقارب من مئة بيتٍ تتضمّن نصائح وحكما ومواعظ تستمدّ أصولها من المفاهيم والمبادئ الإسلامية. سينهج البحثُ المنهج التاريخي الوصفي والتحليلي لدراسة مضمون القصيدة من الاتجاهين الأدبي والفنّي للتوصّل إلى قيمتها الإسلامية ومدى علاقتها بحياتنا الاجتماعية. الكلمات المفتاحية:شعرالزهد-الأدب العربي-الأدب العربي النيجيري-داود أحمد تجاني -القيم الأخلاقية. Abstract: Asceticism is a psychological phenomenon has a major impact in Arabic poetry since the age pre-Islam(jahiliyyah)and when, taken by some of Christians hermits and Abraham, the ideas of asceticism spread under the influence of Christian asceticism hermits and Abraham , and the common part of which was on the tongues of poets, some of these poetry appeared in the poetry of wisdom poems, then the poems, and became his patrons and admirers, and his representatives leave through the ages literary Arabic, but he flourished a remarkable boom in the Abbasid era special factors, including political, social, ethical, cultural, and then take asceticism place high in the purposes of Lyric Arab in every time and place where Raj Arabic literature until modern times. All of this has an impact in Nigerian Arabic literature in particular. This research aims to study the ethical values in the "deltoid ascetic poem" of the late Nigerian poet, Dr David Tijani Odikilin. It contains the poem on nearly one hundred houses with tips and arbitrator and the preaching of their assets derived from the concepts and principles of Islam. This study will follow historical descriptive methodology and analytical study of the content of the poem from both directions (perspectives) of literary and artistic value to arrive at the Islamic and the relevance of our social life. Keywords: Poetry of Asceticism- Arabic Literature- Nigerian Arabic Literature- Daud Ahmad Tijani- Ethical Values. Abstrak: Zuhud adalah salah satu sifat yang mempunyai kesan yang besar di dalam syair Arab sejak zaman jahiliyah yang mana tema ini digunakan oleh orang-orang kristian dan golongan anti berhala sehingga ianya tersebar secara meluas di bawah pengaruh agama masing-masing. Tema ini terkenal di kalangan penyair-penyair dan ia muncul buat pertama kali dalam kompilasi syair-syair hikmah dan sebagainya sehinggalah terbit kompilasi khas yang mengumpulkan syair-syair zuhud. Tema ini terus diminati oleh penyair-penyair dan peminat-peminatnya sepanjang zaman terutamanya ketika era pemerintahan Abbasiyah di sebabkan beberapa faktor seperti politik, sosial, moral dan budaya. Ianya terus mendapat kedudukan yang tinggi di dalam syair –syair Arab di setiap zaman dan tempat sehingga hari ini. Semua ini memberi kesan kepada kesusasteraan Arab di Nigeria terutamanya dalam penulisan puisi. Maka kajian ini bertujuan untuk mengkaji nilai-nilai moral dalam “Puisi-puisi Zuhud” oleh penyair Nigeria Doktor Daud Tijani Adaikilaikun. Puisi ini terdiri daripada hampir seratus rangkap yang mengandungi unsur-unsur nasihat, hikmah dan pengajaran berdasarkan prinsip-prinsip islam. Kajian ini merupakan kajian deskriptif dan analisis sejarah yang mengkaji kandungan puisi dari sudut kesusasteraan dan kesenian sehingga dapat mencapai kedudukan yang tinggi sepertimana yang di kehendaki oleh islam serta mengkaji sejauh mana hubungannya dengan kehidupan masyarakat. Kata kunci: Syair Zuhud- Sastera Arab- Kesusasteraan Arab Nigeria – Daud Ahmad Tijani – Nilai-Nilai Murni.